Some Ideas About Using Mass Media in Adult Education (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2016)
According to Franzmann (1998) the basic cultural industries are always changing in modern society and in education. Understanding the mass media message is a necessity, and it is not possible without critical thinking, which is equal to confident treatment. The up to date literacy and everyday information can be served from mass media taking into consideration the needs of adults. Adults with their age and experiences can use some different learning forms which significantly differ from the tools of formal teaching (Buckingham, 2003). The media is one of these tools if the adults have appropriate methods to analyze media events from news. The education-culture-mass media triangle has a very diverse link, but mass communication has an accepted priority during formal education (McQuail, 2003). Mediandragogy – as a special term – investigates the personality-forming effects and possibility of mass media, which can make adult learning efficient.